2019
DOI: 10.1111/apa.14918
|View full text |Cite
|
Sign up to set email alerts
|

Review about the impact of growing up with a chronic disease showed delays achieving psychosocial milestones

Abstract: Aim This review aimed to provide a comprehensive overview of the psychosocial developmental trajectory of various diseases during childhood and adolescence. Methods Studies of Dutch young adults aged 18‐35 years, who had grown up with a chronic disease, were included if the Course of Life Questionnaire had been used to assess psychosocial developmental milestones in three domains: social, autonomy and psychosexual. Differences between the disease groups and the general population were presented as Cohen's d an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…29 32 We found that social functioning is significantly associated with fatigue, which is consistent with a recent finding that children with a chronic disease generally encounter more difficulties and achieve psychosocial milestones at a later age compared with healthy peers. 29 Unfortunately, our study cannot distinguish whether poorer social functioning precedes or is a consequence of fatigue or whether the two perpetuate one another. Encouraging these children to engage in social participation and helping them selfmanage their disease may empower them to cope with their disease, possibly reducing fatigue.…”
Section: Open Accessmentioning
confidence: 81%
See 1 more Smart Citation
“…29 32 We found that social functioning is significantly associated with fatigue, which is consistent with a recent finding that children with a chronic disease generally encounter more difficulties and achieve psychosocial milestones at a later age compared with healthy peers. 29 Unfortunately, our study cannot distinguish whether poorer social functioning precedes or is a consequence of fatigue or whether the two perpetuate one another. Encouraging these children to engage in social participation and helping them selfmanage their disease may empower them to cope with their disease, possibly reducing fatigue.…”
Section: Open Accessmentioning
confidence: 81%
“…3 5-7 28 Encouraging the child to, for example, engage in a healthy lifestyle and participate in sports may be beneficial on a biological and social level, thereby reducing fatigue. [28][29][30] This is likely true for fatigued children who are in a stable phase of their chronic disease, as well as other patient populations who suffer from fatigue, for example, following COVID-19. 14…”
Section: Discussionmentioning
confidence: 99%
“…Results from a meta‐analysis by Pinquart (2014) showed that young people with chronic paediatric illness had lower rates of completing higher education, finding employment, lower income, leaving the parental home, marrying, and becoming parents compared with healthy peers. In a recent review investigating the achievement of psychosocial developmental milestones such as social, autonomy, and psychosexual domains, the development of young people who had grown up with a chronic disease was delayed in all three domains (Maurice‐Stam et al., 2019). Personal barriers such as physical limitations (Osgood et al., 2010) and environmental barriers (Cook et al., 2016; Stewart et al., 2014; Waldboth et al., 2016) have been reported as roadblocks to a successful transition to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping up with social demands might be challenging for young adults with a chronic condition. A recent review on the impact of growing up with a chronic disease on psychosocial outcomes showed a lower likelihood of having a paid job [28]. Similarly, a study in adults with T1DM showed higher unemployment and sick leave rates among this group compared to the general populationwhile they were slightly better educated [9,29].…”
Section: Discussionmentioning
confidence: 93%